The use of assisted fertilization in Finland : health effects and equity - Klemetti, Reija; Sosiaali- ja terveysalan tutkimus- ja kehittämiskeskus (Tutkimuksia / Sosiaali- ja terveysalan tutkimus- ja kehittämiskeskus, ISSN 1236-0732, 2006)
Abstract (s. 7-8).
Keywords: Ovulation Induction; Embryo Transfer; Risk Factors; Health Status; Abnormalities, Multiple; Pregnancy Outcome; Registries; Ovarian Hyperstimulation Syndrome; Fertilization in Vito; Prenatal Care : economics; Social Justice; Reproductive Techniques, Assisted; Fertilization in Vitro; Fertilization in Vitro : economics; Fertilization in Vitro : utilization; Ovulation Induction : adverse effects; Ovulation Induction : utilization; Infertility; Congenital Abnormalities : epidemiology; Abortion, Spontaneous; Treatment Outcome; Socioeconomic Factors; Private Practice; Community Health Services; Child; Female; Dissertations, Academic; Reproductive Techniques, Assisted : adverse effects; Fertilization in Vitro : adverse effects; Health Services Accessibility; Reproductive Technigues, Assisted; Health Care Costs; hedelmöityshoito; koeputkihedelmöitys; hedelmättömyys; hoito; komplikaatiot; keskenmeno; terveysvaikutukset; sosioekonomiset tekijät; alueelliset erot; oikeudenmukaisuus; käyttö; lapset (ikäryhmät); kustannukset; epämuodostumat; lapsettomuus; väitöskirjat; hoitotiede; yhdenvertaisuus; keinoalkuiset lisääntymismenetelmät; lapset; Suomi; provrörsbefruktning : in vitro fertilisering : ovulationsinduktion : registerundersökning : hälsopåverkan : komplikationer : OHSS : barnens hälsa : medfödda missbildningar : kostnader : rättvisa : IVF : ovulation induction : health effects : register-based study : complications : child health : perinatal health : congenital anomaly : equity : costs